2008
DOI: 10.1111/j.1552-6909.2008.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Sexual Risk With Practice of Periodic Secondary Abstinence

Abstract: Abstract:Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…It is important to begin thinking about how to construct secondary abstinence measures that will gather information which will aid researchers, practitioners, and other health professionals encouraging healthy behaviors that reduce the prevalence of HIV and STIs among young African American women and girls. The studies on secondary abstainers’ motivations that are available (Haglund, 2008; Loewenson et al, 2004; Paradise et al, 2001) have provided a solid foundation on which to build. However, more research is needed to understand secondary abstinence and its role in improving health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to begin thinking about how to construct secondary abstinence measures that will gather information which will aid researchers, practitioners, and other health professionals encouraging healthy behaviors that reduce the prevalence of HIV and STIs among young African American women and girls. The studies on secondary abstainers’ motivations that are available (Haglund, 2008; Loewenson et al, 2004; Paradise et al, 2001) have provided a solid foundation on which to build. However, more research is needed to understand secondary abstinence and its role in improving health.…”
Section: Discussionmentioning
confidence: 99%
“…African American adolescent females participating in an intervention to promote periodic secondary abstinence as a risk reduction strategy reported similar motivations for abstinence (Haglund, 2008). This pilot study included a quantitative survey and in-depth interviews with 17 of 33 participants (mean = 16 years) recruited from two alternative schools serving economically disadvantaged youth with poor academic achievement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence suggests that rather than abandon efforts to help young people avoid sex, we need to find new ways to do so. Innovations in sexual risk reduction education, such as culturally tailored approaches (Villarruel et al 2007), periodic abstinence (Haglund 2008), and increased fertility awareness (Cabezon et al 2005), are in development and more research is indicated.…”
mentioning
confidence: 99%
“…As hypothesized, the AOE group had less favorable sex attitudes immediately post-intervention than the comparison group; however, there was no overall intervention effect. Other studies have demonstrated feasibility in impacting adolescents’ abstinence attitudes through interventions (Borawski, Trapl, Lovegreen, Colabianchi & Block, 2005; Di Noia & Schinke, 2007; Haglund, 2008; Smith et al, 2005). Participants demonstrated more social norms favoring sex over time without regard to intervention type.…”
Section: Discussionmentioning
confidence: 99%